2020
DOI: 10.3390/ijerph17238854
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey in Greece about Knowledge, Risk Perceptions, and Preventive Behaviors for COVID-19 during the General Lockdown in April 2020

Abstract: Background: The aim of this study was to investigate the knowledge, attitudes, and practices of the Greek general population toward coronavirus disease 2019 (COVID-19) during the lockdown period in April 2020, to examine factors associated with misperceptions and to determine behavioral patterns that may require interventions. Methods: A cross-sectional study of the general Greek population (N = 1858) was conducted. A geographically stratified cluster sampling was implemented. A questionnaire was composed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 5 publications
4
30
0
Order By: Relevance
“…The questionnaire was designed based on our previous knowledge [ 14 , 15 ] and done by an expert team comprised of an epidemiologist, an occupational health professional and a public health specialist. To provide feedback on clarity and usefulness of questions included, the questionnaire was pre-tested with 15 HCWs.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was designed based on our previous knowledge [ 14 , 15 ] and done by an expert team comprised of an epidemiologist, an occupational health professional and a public health specialist. To provide feedback on clarity and usefulness of questions included, the questionnaire was pre-tested with 15 HCWs.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is lower than rates reported in other countries, but similar to that of a recent study in Greece which reported that only 28% mentioned wearing a face mask indoors. 5 Hence, additional studies using more recent data are warranted to identify potential changes in COVID-19 related knowledge and attitudes, in the uptake of preventive behaviors and their association. Such studies might further enable policymakers to assess the effectiveness of evolving public health guidelines and initiatives adopted through the first year of the pandemic and make necessary and tailored adjustments.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 7 - 10 The line of research addressing knowledge, attitudes and practices related to COVID-19 pandemic, has substantiated variability across various countries and settings. 2 , 3 , 5 , 6 , 9 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…All studies had a cross-sectional study design: 22 used online surveys [43][44][45][46][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] and one study used a mixed-methods approach, including both an online survey and semi-structured interviews 47 . Eighteen surveys were conducted in the rst half of 2020 (January-June) 43-46,48−53,55-58,62−65 and ve were conducted in the latter half of 2020 (July-December) 45,54,59−61 .…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…Of the 23 studies included in the review, 17 studies used piloted, trialled or previously published survey instruments (Additional File 3) 43,44,47,48,[50][51][52][53][54][55][56][57][58][59][60][61]64,65 . Only 11 studies used an adequate sampling frame to achieve a representative sample 45,46,50,51,[54][55][56]58,59,61,62 and 10 studies were deemed to use an adequate selection process 47,50,51,[54][55][56][57]59,61,62 . Of the studies that used adequate sampling frames, eight used existing online research panels 46,50,54,56,58,59,61,62 (two most common being Qualtrics, n = 2 54,56 and the AmeriSpeak panel, n = 2 50,59 ).…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%